Surface-modified fiber, its manufacturing method, and molded body using surface-modified fiber
Surface-modified fibers with a hydrogen-bonding functional group in their surface layer address the limitations of existing fibers by improving adhesion to resin and concrete, suppressing coloring, and maintaining transparency.
Patent Information
- Application Number
- JP2024560360
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-12-20
- Filing Date
- 2023-12-20
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-12-20
AI Technical Summary
Existing surface-modified fibers used for adhesion to resin and concrete have limitations in adhesion effectiveness and tend to undergo coloring due to high-temperature treatments, while also facing challenges with low adhesion to resins.
A surface-modified fiber with a layer containing a compound having a hydrogen-bonding functional group, applied in an amount of 0.01 to 2.5 parts by mass based on 100 parts by mass of the fiber, which improves adhesion to resin and concrete while suppressing coloring.
The surface-modified fiber achieves excellent adhesion to both resin and concrete, prevents coloring, and maintains transparency, thereby enhancing the performance and application range of the fibers.
Smart Images

Figure 0007670938000001 
Figure 0007670938000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface-modified fiber having excellent adhesion to resin and concrete, a method for producing the same, and a molded article using the surface-modified fiber. [Background technology]
[0002] Synthetic fibers such as polyvinyl alcohol and polyamide are excellent in strength and durability, as well as being lightweight and inexpensive. Therefore, they are used as fibers for reinforcing concrete and the like for the purpose of improving the strength of buildings and preventing cracks. The synthetic fibers are also used as fibers for reinforcing automobile tires, oil brake hoses, etc. When the fibers are used for this purpose, they need to be firmly bonded to the rubber, so surface-modified fibers with modified surfaces are used.
[0003] As a specific example of the surface-modified fiber, Patent Document 1 discloses a fiber coated with branched polyethyleneimine in a proportion of about 0.2 to about 20% by mass based on the total weight of the coated fiber. Patent document 2 describes a reinforcing fiber having a surface modification layer that covers at least a portion of the surface of the fiber, the surface modification layer being characterized in that it contains a specific polyamine compound. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-511602 [Patent Document 2] International Publication No. 2022 / 044460 Summary of the Invention [Problem to be solved by the invention]
[0005] Although the surface-modified fibers described above exhibit a certain degree of performance in terms of adhesiveness, etc., there is room for improvement. Specifically, the fiber described in Patent Document 1 does not have sufficient adhesive strength and improvement is desired, and the fiber described in Patent Document 2 has a problem of discoloration due to treatment at a relatively high temperature. In addition, chemical fibers generally have extremely low adhesiveness and adhesion to resins, so the development of a method for improving these has been desired.
[0006] The present invention has been made in consideration of the above-mentioned conventional problems, and provides a surface-modified fiber that has excellent adhesion to resin and concrete and can suppress coloring, a manufacturing method thereof, and a molded body using the surface-modified fiber. [Means for solving the problem]
[0007] As a result of intensive research to solve the above-mentioned problems, the inventors discovered that by providing a surface modification layer containing a compound having a hydrogen-bonding functional group on at least a portion of the surface of the fiber, the adhesion between the fiber and resin, and between the fiber and concrete, can be improved, and thus completed the present invention.
[0008] That is, the present invention relates to the following [1] to [6]. [1] A surface-modified fiber having a fiber and a surface-modified layer covering at least a part of the surface of the fiber, A surface-modified fiber, characterized in that the surface-modified layer contains a compound having a hydrogen-bonding functional group, and the amount of the surface-modified layer is 0.01 to 2.5 parts by mass per 100 parts by mass of the fiber used as the raw material. [2] The surface-modified fiber according to [1], wherein the hydrogen-bonding functional group is at least one selected from a hydroxyl group, a carboxyl group, a salt of a carboxyl group, an ester of a carboxyl group, an acid anhydride of a carboxyl group, a carbonyl group, an aldehyde group, an acetal of an aldehyde group, an amino group, and an amide group. [3] The surface-modified fiber according to [1] or [2], wherein the fiber is one or more types of fiber selected from polyamide-based fibers, polyvinyl alcohol-based fibers, polyester-based fibers, and regenerated cellulose-based fibers. [4] The hue parameter (YI) of the surface-modified fiber is 0 to 50. The surface-modified fiber according to any one of items [3] to [4]. [5] A method for producing a surface-modified fiber according to any one of [1] to [4] above, comprising the following steps (1) and (2): [Step (1)] A step of preparing a solution or dispersion of the compound having a hydrogen-bonding functional group and applying the solution or dispersion to the fiber. [Step (2)] A step of heat treating the fiber to which the solution or dispersion is applied at 180 to 280° C. for 50 seconds or less. [6] A molded article using the surface-modified fiber according to any one of [1] to [4] above. Effect of the Invention
[0009] The present invention can provide a surface-modified fiber that has excellent adhesion to resin and concrete and can suppress coloring, a manufacturing method thereof, and a molded article using the surface-modified fiber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Surface modified fiber] The surface-modified fiber of the present invention is a surface-modified fiber having a fiber and a surface-modified layer covering at least a part of the surface of the fiber, The surface modification layer contains a compound having a hydrogen-bonding functional group, and the amount of the surface modification layer is 0.01 to 2.5 parts by mass per 100 parts by mass of the fibers used as the raw material. In the present invention, since a surface-modified layer containing a compound having a hydrogen-bonding functional group is provided on at least a part of the fiber surface, a strong affinity is exhibited between the hydrogen-bonding functional group and the fiber, and between the hydrogen-bonding functional group and concrete or resin, resulting in improved adhesion between the fiber and resin, and between the fiber and concrete. In addition, since decomposition of the surface-modified layer is unlikely to occur, it is possible to obtain a surface-modified fiber with excellent transparency. In the present invention, a "surface modification layer covering at least a portion of the surface of the fiber" may mean an embodiment in which a surface modification layer is present on at least a portion of the surface of the fiber, for example, as a membrane or layer, or an embodiment in which the raw material of the fiber contains a component corresponding to the surface modification layer, and the component of the surface modification layer is present on a portion of the surface of the fiber itself.
[0011] <Surface modification layer> The surface modified layer in the present invention is a layer containing a compound having a hydrogen-bonding functional group. In the present invention, by using a compound having a hydrogen-bonding functional group in the surface modified layer, it is possible to improve the adhesive strength between the surface modified fiber and resin, or between the surface modified fiber and concrete. In this specification, the term "hydrogen bond" refers to a bonding interaction formed between a hydrogen atom (donor) that is bonded to an atom with high electronegativity (O, N, S, etc.) and is electrically positively polarized, and an electronegative atom (acceptor) that has a lone pair of electrons.
[0012] Examples of the hydrogen-bonding functional group include a hydroxyl group, an epoxy group, an ether group, a mercapto group, a carboxyl group, a carbonyl group, an aldehyde group, an amino group, an imino group, an imidazole group, a urethane group, an amide group, a urea group, an isocyanate group, a nitrile group, a silanol group, and derivatives thereof. Examples of the carboxyl group include a group derived from a monocarboxylic acid and a group derived from a dicarboxylic acid. Examples of the derivatives of the carboxyl group include a salt thereof, an esterified product thereof, an amidated product thereof, and an acid anhydride thereof. Examples of the derivatives of the aldehyde group include an acetalized product thereof. Examples of the derivatives of the silanol group include an esterified product thereof. Among these, one or more selected from a hydroxy group, a carboxy group, a salt of a carboxy group, an ester of a carboxy group, an acid anhydride of a carboxy group, a carbonyl group, an aldehyde group, an acetal of an aldehyde group, an amino group, and an amide group are preferred, and one or more selected from a carboxy group, a carbonyl group, an amino group, and an amide group are more preferred.
[0013] Specific examples of the compound having a hydrogen-bonding functional group include compounds having a hydroxy group, such as ethylene glycol, diethylene glycol, 1,2-propylene glycol, and 1,3-propylene glycol; Compounds having an amino group, such as polyethyleneimine, polyallylamine, polyvinylamine, polydiallylmethylamine, polydiallylethylamine, and salts thereof; Compounds having an amide group, such as polyvinylpyrrolidone, 2-pyrrolidone, N-methyl-2-pyrrolidone, N-hydroxyethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, and ε-caprolactam; Compounds having a carboxy group, such as maleic acid, fumaric acid, citraconic acid, perpropionic acid, and itaconic acid; Among the compounds having a hydrogen-bonding functional group, polyethyleneimine, polyallylamine, polyvinylpyrrolidone, etc. are preferred. Use of these compounds having a hydrogen-bonding functional group can particularly improve the adhesion and transparency of the surface-modified layer.
[0014] The amount of the compound having a hydrogen-bonding functional group in the surface-modified layer is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably substantially 100% by mass. When the amount of the compound having a hydrogen-bonding functional group in the surface-modified layer is within the above range, it is possible to improve the adhesion between the fiber and the resin, and it is also possible to obtain a surface-modified fiber having excellent transparency.
[0015] From the viewpoint of improving the adhesiveness with the resin, the surface modification layer preferably covers the entire surface of the fiber, but it is sufficient that the surface modification layer substantially covers at least a part of the fiber surface. The specific amount of the surface modification layer covering the fiber surface is 0.01 to 2.5 parts by mass, preferably 0.05 to 2.0 parts by mass, more preferably 0.1 to 1.5 parts by mass, even more preferably 0.15 to 1.2 parts by mass, even more preferably 0.15 to 1.0 parts by mass, and particularly preferably 0.2 to 0.5 parts by mass, relative to 100 parts by mass of the fibers used as the raw material.
[0016] The surface modification layer may or may not contain other components in addition to those described above, such as a crosslinking agent, an acid, a base, an inorganic salt, an organic salt, a pigment, a dye, an antioxidant, a polymerization initiator, and a plasticizer. When the surface modification layer contains the other components, the content of the other components in the surface modification layer is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, from the viewpoint of improving the adhesive strength with the resin.
[0017] Surface modification in the present invention fiber The hue parameter (YI) of the surface is preferably 0 to 50. fiber When the hue parameter (YI) is within the above range, it is possible to obtain a surface-modified fiber having excellent transparency. fiber The hue parameter (YI) is more preferably 0-45, further preferably 0-35, even more preferably 0-30, and particularly preferably 0-25. Surface modification in the present invention fiber The hue parameter (YI) is a hue measured in accordance with JIS Z8722:2009, and specifically, can be measured by the method described in the examples.
[0018] <Textile> The fibers used in the surface-modified fiber of the present invention are not particularly limited, and hydrophilic or hydrophobic fibers can be used. In the present invention, the term "fiber" includes not only short fibers and long fibers, but also nonwoven fabrics, woven fabrics, knitted fabrics, felts, sponges, and other forms.
[0019] Examples of hydrophilic synthetic fibers include synthetic fibers made of a thermoplastic resin having hydrophilic functional groups such as hydroxyl groups, carboxyl groups, sulfonic acid groups, and amino groups, and / or hydrophilic bonds such as amide bonds. Specific examples of such thermoplastic resins include polyvinyl alcohol-based resins, polyamide-based resins (aliphatic polyamides such as polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, polyamide 612, and polyamide 9C (a polyamide composed of nonanediamine and cyclohexanedicarboxylic acid); semi-aromatic polyamides synthesized from aromatic dicarboxylic acids and aliphatic diamines, such as polyamide 9T (a polyamide composed of nonanediamine and terephthalic acid); wholly aromatic polyamides synthesized from aromatic dicarboxylic acids and aromatic diamines, such as polyparaphenylene terephthalamide), and polyacrylamide-based resins). Among these, polyvinyl alcohol-based resins and polyamide-based resins are preferred. The hydrophilic synthetic fibers may be used alone or in combination of two or more. In addition, these hydrophilic synthetic fibers may or may not be subjected to a hydrophilization treatment described below in order to further enhance the hydrophilicity.
[0020] Examples of hydrophilic natural fibers include natural cellulose fibers such as wood pulp, e.g., kraft pulp, and non-wood pulp, e.g., cotton pulp and straw pulp. Hydrophilic regenerated fibers include regenerated cellulosic fibers such as rayon, lyocell, cupra, and polynosic. These natural fibers and regenerated fibers may be used alone or in combination of two or more. Furthermore, these hydrophilic natural fibers and regenerated fibers may or may not be subjected to a hydrophilization treatment described below in order to further enhance the hydrophilicity.
[0021] The hydrophilic fiber may have at least a hydrophilic surface, and may be, for example, a hydrophobic fiber whose surface has been hydrophilized, a core-sheath type composite fiber in which a hydrophobic resin is used as the core and a hydrophilic resin is used as the sheath, or a single-structure non-composite fiber that does not have a core-sheath type structure. For examples of hydrophilic resins that constitute the sheath, see the description of hydrophilic synthetic fibers. Examples of hydrophobic fibers made of hydrophobic resins include the hydrophobic fibers described below.
[0022] The hydrophilization treatment is not particularly limited as long as it is a treatment that chemically or physically imparts hydrophilic functional groups to the fiber surface. For example, the hydrophilization treatment can be a method in which a hydrophobic fiber made of a hydrophobic resin described below is modified with a compound or a derivative thereof that contains a hydrophilic functional group such as an isocyanate group, an epoxy group, a hydroxyl group, an amino group, an ether group, an aldehyde group, a carbonyl group, a carboxyl group, or a urethane group, or a method in which the surface is modified by electron beam irradiation.
[0023] In the present invention, it is also possible to use hydrophobic fibers that could not be strongly adhered to resins using conventional techniques. Hydrophobic fibers generally do not have polar functional groups on their fiber surfaces, and therefore have poor affinity with adhesive components described below, and cannot be strongly adhered to resins. However, by providing a surface modification layer on the fiber surface as in the present invention, even hydrophobic fibers can be strongly adhered to resins.
[0024] Examples of hydrophobic fibers that can be used in the present invention include polyolefin fibers such as polyethylene and polypropylene, polyester fibers such as polyethylene terephthalate, and wholly aromatic polyester fibers. Among these, polyester fibers are preferred because they are excellent in terms of production cost, strength, heat resistance, durability, and the like.
[0025] In the present invention, among the above-mentioned fibers, synthetic fibers and regenerated fibers are preferred, and among them, one or more types of fibers selected from polyamide fibers, polyvinyl alcohol fibers, polyester fibers, and regenerated cellulose fibers are preferred. In the present invention, one type of fiber may be used alone, or two or more types may be used in combination. The fibers used in the surface modified fiber of the present invention preferably have a single filament fineness of 500 to 4,500 dtex. If the single filament fineness is 500 dtex or more, it is easy to produce industrially. Also, if the single filament fineness is 4,500 dtex or less, the strength of the surface modified fiber is easily maintained when it is used as a reinforcing material. From the above viewpoint, the fiber used in the surface modified fiber of the present invention more preferably has a single fiber fineness of 500 to 4,000 tex, and further preferably 1,000 to 3,000 tex.
[0026] [Method of manufacturing surface modified fibers] The surface-modified fiber of the present invention is preferably produced by a production method having the following steps (1) and (2). When produced by the method having the following steps, it is possible to produce a surface-modified fiber while preventing decomposition of the surface-modified layer, so that the fiber has excellent adhesive strength and is capable of suppressing coloration. [Step (1)] A step of preparing a solution or dispersion of the compound having a hydrogen-bonding functional group and applying the solution or dispersion to the fiber. [Step (2)] A step of heat treating the fiber to which the solution or dispersion is applied at 180 to 280° C. for 50 seconds or less.
[0027] In the step (1), the solvent or dispersion medium in which the compound having a hydrogen-bonding functional group is dissolved or dispersed is not particularly limited, but from the viewpoints of storage stability and cost, water or a water-soluble organic solvent is preferred. Examples of the water-soluble organic solvent include organic solvents such as monohydric alcohols having 1 to 8 carbon atoms, such as methanol, ethanol, isopropanol, n-butanol, isopentyl alcohol, and tertiary butanol, polyhydric alcohols such as ethylene glycol, diethylene glycol, and glycerin, ketones having 3 to 10 carbon atoms, such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone, and carbonate-based organic solvents, such as propylene carbonate. Among these, water and alcohols having 1 to 6 carbon atoms are more preferred, and water is even more preferred.
[0028] The amount of the compound having a hydrogen-bonding functional group when dissolving or dispersing the compound having a hydrogen-bonding functional group in the solvent or dispersion medium is preferably 0.01 to 30 parts by mass, more preferably 0.05 to 20 parts by mass, even more preferably 0.1 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the solvent or dispersion medium. When the amount of the compound having a hydrogen-bonding functional group relative to 100 parts by mass of the solvent or dispersion medium is within the above range, it becomes possible to uniformly attach the compound having a hydrogen-bonding functional group to the fiber while suppressing production costs.
[0029] In the step (1), the method for applying the solution or dispersion of the compound having a hydrogen-bonding functional group to the fiber is not particularly limited, and it is preferable to apply the solution or dispersion by at least one method selected from, for example, immersion, a roll coater, an oiling roller, an oiling guide, nozzle (spray) application, brush application, and the like.
[0030] The temperature of the heat treatment in the step (2) is preferably 180 to 280° C., more preferably 190 to 270° C., and further preferably 200 to 260° C. The heat treatment temperature is preferably 220 to 250° C., and more preferably 230 to 250° C. If the heat treatment temperature exceeds the upper limit, coloration occurs due to thermal decomposition. On the other hand, if the heat treatment temperature is below the lower limit, sufficient adhesiveness is not achieved.
[0031] The heat treatment time is preferably 0.1 to 50 seconds, more preferably 1 to 45 seconds, even more preferably 2 to 40 seconds, even more preferably 3 to 35 seconds, even more preferably 3 to 20 seconds, and even more preferably 3 to 10 seconds. If the heat treatment time exceeds the upper limit, coloring occurs due to thermal decomposition. On the other hand, if the time is less than the lower limit, adhesion may decrease. When the heat treatment time is set to a short time of 30 seconds or less, the treatment can be carried out online using a heat treatment furnace in the production process of polyvinyl alcohol-based fibers.
[0032] In the production of surface-modified fibers, the heat treatment may be carried out once, or may be carried out two or more times at different temperatures and times. However, multiple heat treatments at high temperatures may cause the surface-modified layer to decompose, which may result in coloration or a decrease in adhesive strength.
[0033] <Physical properties of surface-modified fibers> In the present invention, the surface-modified fibers can be in various shapes depending on the application. For example, they may be short fibers such as cut fibers, or long fibers. In the case of long fibers, it is also a preferred embodiment that they are multifilaments.
[0034] The strength of the surface-modified fiber is preferably 4 to 30 cN / dtex, and more preferably 5 cN / dtex or more. The strength of the surface-modified fiber of the present invention can be measured by the method described in the Examples.
[0035] The surface-modified fiber of the present invention can be used in any shape, but is preferably used in the form of a fiber cord, woven fabric, knitted fabric, etc., which contains the surface-modified fiber at least in part, and is more preferably used as a woven fabric or knitted fabric which contains the surface-modified fiber at least in part. For example, it can also be used as a surface-modified fiber to be embedded in resin, cement, etc., as described below.
[0036] [Molded body] The molded article of the present invention is not particularly limited as long as it uses the surface-modified fiber. Since the surface-modified fiber has excellent adhesion to resin, it is preferable to use a molded article having the surface-modified fiber and a resin layer. From the viewpoint of maintaining the shape of the resin, the surface-modified fiber used in the molded article is preferably used as a woven or knitted fabric containing the surface-modified fiber at least in part, and more preferably used as a part of a laminate in which a reinforcing layer made of the woven or knitted fabric and a resin layer are laminated.
[0037] The resin used in the molded article of the present invention is not particularly limited, and examples thereof include polyolefin resins such as polyethylene resin, polypropylene resin, and polybutylene resin; methacrylic resins such as polymethyl methacrylate resin; polystyrene resins such as polystyrene resin, ABS resin, and AS resin; polyester resins such as polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polytrimethylene terephthalate resin, polyethylene naphthalate (PEN) resin, and poly 1,4-cyclohexyldimethylene terephthalate (PCT) resin; polyamide (PA) resins such as 6-nylon resin, 6,6-nylon resin, and PA9T; polyvinyl chloride resin, polyoxymethylene (POM) resin, polycarbonate (PC) resin, and polyphenylene sulfide resin. Examples of the resins include polyphenylene ether (PPS) resin, modified polyphenylene ether (PPE) resin, polyetherimide (PEI) resin, polysulfone (PSF) resin, polyethersulfone (PES) resin, polyketone resin, polyarylate (PAR) resin, polyethernitrile (PEN) resin, polyetherketone (PEK) resin, polyetheretherketone (PEEK) resin, polyetherketoneketone (PEKK) resin, polyimide (PI) resin, polyamideimide (PAI) resin, fluorine (F) resin; liquid crystal polymer resin such as liquid crystal polyester resin; thermoplastic elastomer such as polystyrene, polyolefin, polyurethane, polyester, polyamide, polybutadiene, polyisoprene, or fluorine; or copolymer resin or modified resin thereof. These resins may be used alone or in combination of two or more. Among these, polyvinyl chloride resin is preferred from the viewpoint of improving adhesion to the surface-modified fiber.
[0038] The molded article of the present invention may be a fiber-reinforced resin obtained by mixing the surface-modified fiber with a resin. The resin used for the fiber-reinforced resin may be the resin described above. When the molded article of the present invention is a fiber-reinforced resin, the content of the surface-modified fiber relative to 100 parts by mass of the resin is preferably 0.1 to 50 parts by mass, more preferably 1 to 30 parts by mass. When the amount of the surface-modified fiber relative to the resin is within the above range, the dispersibility of the surface-modified fiber in the resin is good, and an excellent reinforcing effect is exhibited.
[0039] There is no particular limitation on the method of incorporating the surface-modified fiber of the present invention into the resin, and for example, a method of adding the surface-modified fiber to the pellets of the resin and mixing them uniformly. The method of producing the fiber-reinforced resin is also not particularly limited, and molding methods such as melt extrusion molding and injection molding can be used.
[0040] The resin used in the molded article of the present invention may contain additives such as an impact resistance improver, an inorganic filler, etc. Examples of additives include flame retardants, electrical conductivity imparting agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration damping materials, antibacterial agents, insect repellents, deodorants, coloring inhibitors, heat stabilizers, release agents, antistatic agents, lubricants, colorants, and foaming agents. When the additive is used, the content thereof is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, relative to 100 parts by mass of the resin. When the content of the additive is within the above range, the effect of the additive can be obtained while maintaining the reinforcing effect of the surface-modified fiber. EXAMPLES
[0041] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. <Textile> Polyvinyl alcohol fiber (PVA) Kuraray Co., Ltd., Kuraron 5501 (2000dtex, 1000f) Polyamide fiber (PA) Melt-spun nylon 6 (1400dtex, 204f)
[0042] <Compounds having hydrogen-bonding functional groups> [Polyethyleneimine (PEI)] Polyethyleneimine (1) "Epomin P-3000" manufactured by Nippon Shokubai Co., Ltd. Polyethyleneimine (2) "Epomin SP-200" manufactured by Nippon Shokubai Co., Ltd.
[0043] [Polyvinylpyrrolidone (PVP)] Polyvinylpyrrolidone K-85 manufactured by Nippon Shokubai Co., Ltd. [Polyallylamine] "PAA-15" manufactured by Nittobo Medical Co., Ltd.
[0044] <Method for preparing a solution containing a compound having a hydrogen-bonding functional group> The solution used in Example 1 was prepared by mixing 14.3 g of polyethyleneimine (1) and 985.7 g of water. In other Examples and Comparative Examples, the compounds shown in Table 1 were used to prepare aqueous solutions for forming the surface modification layer in the same manner.
[0045] <Example 1> Polyvinyl alcohol-based fibers (PVA-based fibers) were immersed in an aqueous solution containing a compound having a hydrogen-bonding functional group, and then the liquid was squeezed out with a roller. The resulting fiber cord was dried at 140°C for 30 seconds. It was then heat-treated at 240°C for 5 seconds and wound up to produce a surface-modified fiber.
[0046] <Examples 2 to 7, Comparative Examples 1 to 2> A surface-modified fiber was produced in the same manner as in Example 1, except that the production conditions and heat treatment conditions were changed to those shown in Table 1.
[0047] The fibers obtained in the examples and comparative examples were evaluated according to the following methods. The results are shown in Table 1. <Evaluation method> [Hue parameter (YI)] The hue parameter (YI) of the obtained surface-modified fiber was measured using a haze meter SH7000 (manufactured by Nippon Denshoku Kogyo Co., Ltd.) in accordance with JIS Z8722:2009. The values of three points of the surface-modified fiber were measured, and the arithmetic average value was adopted as the hue parameter (YI). The results are shown in Table 1.
[0048] [Strength] According to the test method of JIS L-1013:2010, the strength of the obtained surface-modified fiber was measured in air at 20°C with a yarn length of 20 cm, an initial load of 0.25 g / d, and a pulling speed of 50% / min. The arithmetic average of the measured values at five points was used as the value for this evaluation. The fiber thickness (dtex) was determined by the mass method.
[0049] [Interfacial shear stress] A resin for evaluation was prepared by adding 1% by mass of a curing agent to an unsaturated polyester resin (manufactured by Nippon Tokushu Toryo Co., Ltd.) and stirring it. The resin for evaluation obtained was attached in the form of beads so as to surround the obtained surface-modified fiber, and left at room temperature (20°C) for 2 hours. Then, it was heat-treated at 70°C for 2 hours. The fiber diameter and axial length (resin diameter) of the obtained sample were measured, and then the sample was fixed to a mount and the adhesive strength was measured using a testing machine (INSTRON "Universal Material Testing Machine 3365"), and the interfacial shear stress was calculated using the following formula. Interface shear stress (N / mm 2 ) = Maximum detection load (N) / (π x fiber diameter (mm) x axis length (mm))
[0050] [Process passability] In each example and comparative example, an aqueous solution containing a compound having a hydrogen-bonding functional group was applied to each fiber, and 5 kg of the surface-modified fiber was wound up. The degree of contamination (gum-up) of the support roller through which the surface-modified fiber had passed was evaluated according to the following criteria. ·standard G (good): There is no roller contamination due to gum-up, or contamination is minimal, and there is no problem with spinning operability. B (bad): Roller contamination due to gum-up is significant, single yarns are taken off during spinning, and there is a problem with spinning operability.
[0051] [Table 1]
[0052] <Examples 8 and 9> Surface-modified fibers were prepared in the same manner as in Example 1, except that the compounds having hydrogen-bonding functional groups shown in Table 2 were used. The obtained surface-modified fibers were then twisted at 120 times / m and aligned at 36 fibers / inch to prepare a curtain-like sample. The sample was overlapped with a soft polyvinyl chloride resin sheet and heated at 1 MPa pressure and 160°C for 10 minutes to obtain a test piece. The obtained test piece was adjusted to a width of 1 inch and the peel strength (N / inch) was measured using a measuring machine (INSTRON "Universal Material Tester 3365"). The results are shown in Table 2. The larger the measurement result, the greater the adhesive strength between the surface-modified fiber and the polyvinyl chloride resin.
[0053] <Comparative Example 3> A sample was prepared in the same manner as in Example 8 except that no surface modification treatment was carried out, and the peel strength was measured. The results are shown in Table 2.
[0054] [Table 2]
[0055] As is clear from the results of the Examples and Comparative Examples, the present invention provides surface-modified fibers that are excellent in adhesiveness and can suppress coloration.
Claims
1. A surface-modified fiber having a fiber and a surface-modified layer covering at least a part of the surface of the fiber, the surface modification layer contains one or more compounds having a hydrogen-bonding functional group selected from polyethyleneimine, polyvinylpyrrolidone, and polyallylamine; The amount of the surface modification layer is 0.01 to 2.5 parts by mass per 100 parts by mass of the fibers used as the raw material, The surface-modified fiber is characterized in that the fiber is a polyvinyl alcohol-based fiber.
2. 2. The surface modified fiber according to claim 1, wherein the hue parameter (YI) is 0 to 50. The surface-modified fiber according to claim 1.
3. The method for producing a surface-modified fiber according to claim 1, comprising the following steps (1) and (2): [Step (1)] A step of preparing a solution or dispersion of the compound having a hydrogen-bonding functional group and applying the solution or dispersion to the fiber. [Step (2)] A step of heat treating the fiber to which the solution or dispersion is applied at 180 to 280° C. for 50 seconds or less.
4. A molded article using the surface-modified fiber according to claim 1.
5. The surface-modified fiber; Resin or cement; The molded article according to claim 4, wherein
6. The molded body according to claim 4 , wherein the surface-modified fibers are embedded in a resin or cement.
7. The molded article according to claim 4 , comprising the surface-modified fiber and a resin layer.
Citation Information
Patent Citations
JP1971041450B
JP1973035607A
JP1973035608A
JP1974023273A
Radial tire for heavy load
JP1987163806A